The importance of right ventricular function in patients with pulmonary arterial hypertension. (3rd October 2018) - Badagliacca, Roberto; Papa, Silvia; Poscia, Roberto; Pezzuto, Beatrice; Manzi, Giovanna; Torre, Roberto; Fedele, Francesco; Vizza, Carmine Dario
ABSTRACT: Introduction : Pulmonary arterial hypertension (PAH) is a progressive, life-threatening, and incurable disease. Its prognosis is based on right ventricular (RV) function. Therefore, adequate assessment of RV function is mandatory. Areas covered : This article presents the case of a patient with PAH in which the traditional diagnostic approach did not provide a complete assessment of RV function. The authors show how the analysis of other parameters yielded additional information that improved the management of this patient. Expert commentary : Despite current treatments, PAH often worsens due to progressive RV dysfunction. Appropriate assessment of RV function may facilitate the early identification of patients at risk of RV function impairment. More aggressive treatment of PAH might delay progression of the disease. Traditional risk stratification, which is based on New York Heart Association/World Health Organization (NYHA/WHO) functional class evaluation, the 6-minute walk test, and right heart catheterization, proves insufficient in many PAH patients, as it does not provide complete information about RV function. Thus, further parameters are required. Analysis of RV function, in addition to echocardiography and cardiopulmonary exercise testing, may add relevant prognostic information and improve therapy.